Seebeck coefficients in CuFeS2 thin films by first-principles calculations. (12th June 2019) - Takaki, Hirokazu; Kobayashi, Kazuaki; Shimono, Masato; Kobayashi, Nobuhiko; Hirose, Kenji; Tsujii, Naohito; Mori, Takao
Abstract: We analyze electronic contributions to thermoelectric properties of CuFeS2 thin films. The Seebeck coefficients, electronic structures, and electrical conductances are obtained using the first-principles calculations. All calculations are based on density functional theory, and nonequilibrirum Green's function formalism within the linear response regime for the electronic transport calculations. Electronic structures of thin films oriented to [001] and [100] in three different magnetic phases; non-, ferro-, and antiferro- are examined. All the calculated systems are metallic, and antiferromagnetic electronic states are most stable. Calculated electrical conductances reach to twice larger than that in the bulk, however, the calculated Seebeck coefficients in thin films are suppressed by the metallicity, remain maximally to about a half of the results in the bulk.